2020
DOI: 10.1002/minf.202000093
|View full text |Cite
|
Sign up to set email alerts
|

Antihypoxic Action of Panax Japonicus, Tribulus Terrestris and Dioscorea Deltoidea Cell Cultures: In Silico and Animal Studies

Abstract: Chemical diversity of secondary metabolites provides a considerable variety of pharmacological actions with a significant extension due to their combinations in plant extracts. Production of plant‐derived medicinal products in cell cultures has advantages because of the efficient use of different biotic and abiotic elicitors and better control of the developmental processes. Using PASS software, we predicted biological activity spectra for phytoconstituents identified in cell cultures of Panax japonicus (12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The fifth (n = 10) and sixth (n = 10) groups received an equivalent volume of 0.9% sodium chloride. The doses of cell samples were selected based on the results of the previous study [32].The blood-glucose level was measured before the start of the experiment and after oral administration of cell preparation or metformin every 30 min for 2.5 h.…”
Section: Adrenaline Model Of Hyperglycemiamentioning
confidence: 99%
See 1 more Smart Citation
“…The fifth (n = 10) and sixth (n = 10) groups received an equivalent volume of 0.9% sodium chloride. The doses of cell samples were selected based on the results of the previous study [32].The blood-glucose level was measured before the start of the experiment and after oral administration of cell preparation or metformin every 30 min for 2.5 h.…”
Section: Adrenaline Model Of Hyperglycemiamentioning
confidence: 99%
“…Suspension cell cultures with the ability to produce triterpene and steroidal glycosides have been developed in our laboratory as a sustainable source of biomass and bioactive ingredients of these species [26][27][28][29][30], and their biochemical profiles have been investigated by using various methods [21,[28][29][30][31]. Recently, Lagunin et al [32] suggested high antihypoxic activity of phytopreparations based on P. japonicus, D. deltoidea and T. terrestris cell cultures that, in the case of P. japonicus and T. terrestris, exceeded the effect of the reference drug Mexidol. In addition, the cell biomass of D. deltoidea showed low toxicity in rats when administered orally even at high doses, up to 5 g/kg animal body weight [25].…”
Section: Introductionmentioning
confidence: 99%
“…Their pharmacological profile is presented in Tables 16 and 17. Carbon-bridged steroids, called taccalonolides (265)(266)(267)(268)(269)(270)(271), are a class of microtubulestabilizing agents that exhibit selective cancer-fighting properties [233]. Tacca species are known to contain highly oxygenated ixocarpalactone-type steroids, with an additional ring formed by a carbon-carbon bond between C-16 and C-24, taccalonolide A being the first example of these compounds [120].…”
Section: Miscellaneous Cyclosteroids and Triterpenoids Derived From Marine And Terrestrial Sourcesmentioning
confidence: 99%
“…Freely available via the Internet, PASS Online web-service [264] is used by more than thirty thousand researchers from almost a hundred countries to determine the most promising biological activities for both natural and synthetic compounds [258][259][260]265]. To reveal the hidden pharmacological potential of the natural substances, we are successfully using PASS for the past fifteen years [266][267][268][269][270].…”
Section: Comparison Of Biological Activities Of Natural and Synthetic Cbs And Triterpenoidsmentioning
confidence: 99%
“…A higher value of Pa reects the signicant biological effect experimentally and vice versa. 48,49 The structure of all the iden-tied phytoconstituents (20 compounds) were obtained from the PubChem database. The structures were submitted using the SMILES format and were subjected to the evaluation of the biological activity spectrum, including the anticancer activity.…”
Section: Hplc-uv Analysis Of Characterised Compounds In Crude Methanolic Extracts Of a Nallamalayanamentioning
confidence: 99%